INVESTIGATING EFL SECONDARY STUDENTS’ PERCEPTION IN LEARNING ENGLISH DURING THE COVID-19 PANDEMIC - Chaerani Chaerani; Fauzi Miftakh; Kelik Wachyudi (PROJECT (Professional Journal of English Education), 2022)
A research study that raises issues regarding the challenges faced by students regarding the online learning system due to the pandemic. There are two participants who will be interviewed in this study. Semi-structured interview is the type of interview chosen in this research study there will be three indicators in making interview questions; emotional experiences, the challenges faced, how to deal with the problems. Phenomenology is the research design chosen by the researcher to conduct this research study, and thematic analysis is the method used to analyze the data. From the data that has been taken, the results describe that students are not happy to take part in online learning, because of several obstacles felt by students. Keywords:  Students’ Perception, English Learning Strategies, COVID-19 Pandemic